UPAYA PENINGKATAN KUALITAS PENDIDIKAN DENGAN PENERAPAN KEDISIPLINAN GURU DI SD MUHAMMADIYAH 9 “PANGLIMA SUDIRMAN” MALANG - Ayu Agustin; Muhammad Hasyim Ashari (ABDI MAKARTI, 2023)
As an effort to improve the quality of education is the discipline of teachers. Increasing teacher discipline in the teaching and learning process is expected to improve the quality and quality of education in order to give birth to the next generation who are superior and have good morals. This community service activity was carried out at SD Muhammadiyah 9 "Panglima Sudirman" Malang with the following stages: observing and mapping disciplinary actions, conducting studies on alternative solutions in policy formulation, awareness of the importance of discipline for teachers, and consultation or assistance. The implementation of this activity went well with the result that the teacher carries out his duties and obligations with full sincerity, awareness, patience and a sense of responsibility, because he realizes that discipline in the world of education is important and must start from the teacher as a teacher, to be able to create superior human resources and beneficial to the nation, state and society. The discipline of teachers at SD Muhammadiyah 9 "Panglima Sudirman" Malang is quite good, although there are still some teachers who lack discipline in complying with the rules set by the school. Socialization and coaching continues to be pursued by the school in order to reduce cases of disciplinary violations, with the aim of creating a good educational environment and being a good role model for students at SD Muhammadiyah 9 "Panglima Sudirman" Malang. Keywords: discipline, education, teacher, quality, qualified.